Theoretical and methodological principles of environmental responsibility of small and medium-sized enterprises system's development - Cherednyk, Anna; Vdovenko, Nataliia; Kalinichenko, Sergiy; Matieiev, Pavlo; Makieiev, Oleksandr (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article examines the functioning of SMEs and the principles of forming their environmental responsibility system. The purpose of the study is to analyze, systematize, and improve the theoretical and methodological foundations for developing an ecological responsibility system for SMEs in Ukraine; to determine the sectoral specificity of environmental impacts generated by SMEs; and to substantiate directions for shaping environmental responsibility systems across Ukraine's sectors of the economy. To achieve this goal, the article examines the peculiarities of SMEs' functioning across economic sectors in Ukraine. It analyses the contribution of SMEs to the national economy by economic activity over 2020-2024, identifying sectoral differentiation in their roles and in specific resource consumption patterns. It is substantiated that SMEs ensure the structural flexibility of the economy, generate most jobs, stimulate innovation, and promote regional economic development. The analysis of SME production volumes across sectors demonstrated structural shifts driven by the war, digitalization, and changing market conditions. It was identified that the environmental burden from SMEs is associated with the high material and energy intensity of their operations, as well as limited resources for implementing “green” technologies.

Статтю присвячено вивченню аспектів функціонування МСП та засадам формування їх системи екологічної відповідальності. Стаття має на меті проаналізувати, систематизувати та удосконалити теоретико-методичні засади формування системи екологічної відповідальності МСП в Україні, визначити галузеву специфіку екологічного навантаження від МСП та обґрунтувати напрями формування систем екологічної відповідальності по галузях економіки України. Для досягнення поставленої мети в статті розглянуто особливості функціонування МСП в Україні по галузях. Проаналізовано внесок МСП в національну економіку країни за видами діяльності, часовий відрізок аналізу 2020-2024 рр., виявлено галузеву диференціацію їх ролі та специфіку ресурсоспоживання. Обґрунтовано, що МСП забезпечують структурну гнучкість економіки, формують більшість робочих місць, стимулюють інноваційний розвиток та сприяють регіональній економічній активізації. Дослідження обсягів виробництва МСП за галузями показало структурні зсуви під впливом війни, цифровізації та змін ринкової кон’юнктури. Виявлено, що екологічне навантаження від МСП пов’язано із високою матеріалоємністю та енергоємністю їх діяльності та обмеженістю ресурсів для впровадження «зелених» технологій.
Теоретико-методичні засади формування системи екологічної відповідальності малих та середніх підприємств
Keywords: SME's sector; environmental responsibility; sustainable development; environmental risks; environmental burden; green transformation; сектор МСП; екологічна відповідальність; сталий розвиток; екологічні ризики; екологічне навантаження; зелена трансформація